Human-accelerated weathering increases salinization, major ions, and alkalinization in fresh water across land use. (August 2017) - Kaushal, Sujay S.; Duan, Shuiwang; Doody, Thomas R.; Haq, Shahan; Smith, Rose M.; Newcomer Johnson, Tamara A.; Newcomb, Katie Delaney; Gorman, Julia; Bowman, Noah; Mayer, Paul M.; Wood, Kelsey L.; Belt, Kenneth T.; et al.
Abstract: Human-dominated land uses can increase transport of major ions in streams due to the combination of human-accelerated weathering and anthropogenic salts. Calcium, magnesium, sodium, alkalinity, and hardness significantly increased in the drinking water supply for Baltimore, Maryland over almost 50 years (p < 0.05) coinciding with regional urbanization. Across a nearby land use gradient at the Baltimore Long-Term Ecological Research (LTER) site, there were significant increases in concentrations of dissolved inorganic carbon (DIC), Ca 2+, Mg 2+, Na +, SO4 2−, Si, and pH with increasing impervious surfaces in 9 streams monitored bi-weekly over a 3–4 year period (p < 0.05). Base cations in urban streams were up to 60 times greater than forest and agricultural streams, and elemental ratios suggested road salt and carbonate weathering from impervious surfaces as potential sources. Laboratory weathering experiments with concrete also indicated that impervious surfaces increased pH and DIC with potential to alkalinize urban waters. Ratios of Na + and Cl − suggested that there was enhanced ion exchange in the watersheds from road salts, which could mobilize other base cations from soils to streams. There were significant relationships between Ca 2+, Mg 2+, Na +, and K + concentrations and Cl −, SO4 2-, NO3 − and DIC across land use (p < 0.05), which suggested tight coupling of geochemical cycles. Finally, concentrations of Ca 2+, Mg 2+, DIC, and pH significantly increased with distance downstream (p < 0.05) along a stream network draining 170 km 2 of the Baltimore LTER site contributing to river alkalinization. Our results suggest that urbanization can dramatically increase major ions, ionic strength, and pH over decades from headwaters to coastal zones, which can impact integrity of aquatic life, infrastructure, drinking water, and coastal ocean alkalinization. Graphical abstract: Highlights: Base cations increased in drinking water over ∼50 years coinciding with urbanization. DIC, cations, Si, SO4 2- and pH in streams increased with impervious surface cover. Road salts and weathering of impervious surfaces were major sources of ions. Base cations and pH contributed to alkalinization from headwaters to coastal waters. Increased ions impact drinking water, infrastructure, and coastal alkalinization.